Analisis Hukum Ekonomi Syariah Terhadap Jual Beli Melalui Media Online Di Kalangan Mahasiswa - Zuhrotul Mahfudhoh; Lukman Santoso (LPMP Imperium, 2020)
Purpose: This study aims to find out (1) how IAIN Ponorogo students think about buying and selling online and (2) how the analysis of sharia economic law against buying and selling through online media among IAIN Ponorogo students. Methods: This research is field research with a qualitative approach because it explains the actual state of the research which produces descriptive data in the form of observed words and behavior. Findings: The results of the study were analyzed by the deductive method, which starts with general facts and then ends with a special conclusion. The conclusion of the research is based on the first problem formulation that online sellers and buyers feel the benefits of online media that are very easy, practical, time-saving, cheaper, and do not require capital for online sellers. Implications: This study formulation of the second problem is that basically buying and selling meets directly between the seller and the buyer. However, according to the development of the era of buying and selling through online media, including aspects of muamalah which are permissible unless there is an argument that forbids them.